A 4-Year Retrospective Study Of Dengue And Chikungunya In Tertiary-Care Hospital Of East Delhi - Meena, Manoj Kumar; Mohapatra, Subhashree; Das, Shukla; Singh, N P (Annals of Pathology and Laboratory Medicine, 2023)
Backgound Dengue is a vector-borne disease caused by the dengue virus (DENV, 1–4 serotypes), an arbovirus from flaviviridae family and chikungunya virus is an alphavirus. Material and Methods A 4 year retrospective study was conducted from January 2017 to December 2020 to determine the prevalence of the disease among in-patients and OPD patients. NS1 ELISA for invitro diagnostic kit was used to detect anti-dengue immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies from 2017-2018. Bio-Rad Dengue NS1 Ag ELISA kit was employed for 2019-2020. Results There were 5110 samples were received of which 1269 (24.8%) were laboratory-confirmed as DEN infections. The most common affected age group was 21-40 years old. In terms of gender distribution females were more affected with both dengue and chikungunya as compared to males. Results showed that 28.74% of patients were seropositive in 2017. The maximum seropositivity was observed in 2018 with 36.97% and minimum seropositivity observed in 2020 with 3.43%. Conclusion Further epidemiological studies are required to determine the true burden of these infections.